The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12288-014-0456-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytopenia and Bone Marrow Dysplasia in a Case of Wilson’s Disease

Abstract: We describe a sixteen year old with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Clinically, relevant coagulopathy due to primary pathology has not been reported. However, pancytopenia, including thrombocytopenia, is a known adverse effect of penicillamine therapy [4]. Deranged coagulation parameters with superimposed penicillamine-induced pancytopenia may be a cause of ICH as seen with our patient.…”
mentioning
confidence: 52%
“…Clinically, relevant coagulopathy due to primary pathology has not been reported. However, pancytopenia, including thrombocytopenia, is a known adverse effect of penicillamine therapy [4]. Deranged coagulation parameters with superimposed penicillamine-induced pancytopenia may be a cause of ICH as seen with our patient.…”
mentioning
confidence: 52%
“…At the age of 11.3 years, she was found to have severe anemia by the local heamatologist, without hemolysis or hemorrhage. She received erythrocyte transfusion, no cessation of zinc, which did not improve hypocupremia and anemia obviously, as Rau AR reported that anemia following penicillamine in a WD patient did not respond to treatment with hematinics [13]. The mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients were adults. The only child among them was a 16-year-old boy who had anemia after initial penicillamine therapy for 2 year and anemia worsened after switching to high dose zinc for 9 months [13]. Five patients received over-dose zinc, while three received conventional dose.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia and neutropenia were the most common hematologic abnormalities identified in copper deficiency patients[29,30]. It was considered that hypocupremia may be a reversible cause of bone marrow dysplasia that caused cytopenia[31]. Hypocupremia induced bone marrow dysplasia may be involved in thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%